Perancangan Sistem Informasi Warehouse Dalam Meningkatkan Efisiensi Supply Chain Management Di PT. Elco Indonesia Sejahtera - Dinar Rahayu; Elin Rosliani; Asri Nur Sya'bani (LPPM STMIK Bandung, 2024)
The intense competition in business and the increasing complexity of supply chains require companies to adopt efficient information systems. This study aims to design a warehouse information system for PT. Elco Indonesia Sejahtera, a leather tanning manufacturer, to enhance warehouse management and support supply chain operations. The current manual system presents several challenges, such as recording errors, lack of data integration, and inaccurate information. Using the waterfall method, the research includes needs analysis, design, implementation, and evaluation. The developed system features stock management, item classification, packaging, and shipping, supported by real-time information to accelerate decision-making. The system is designed to improve operational efficiency, reduce costs, and enhance accuracy and speed in logistics processes. The implementation results indicate that the warehouse information system effectively addresses existing operational challenges and supports the company in managing the supply chain more efficiently. Through this optimization, the company is expected to increase competitiveness and respond to market demands more quickly and accurately.